2018
DOI: 10.1016/j.ijrmhm.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Strength and deformation mechanism of tungsten wires exposed to high temperature annealing: Impact of potassium doping

Abstract: Recent efforts dedicated to the assessment of mechanical properties of tungsten wires, as means for fiber-reinforced composites, have shown that potassium (K) doping in the as-drawn state does not modify the mechanical properties of the wire. High temperature annealing (Ta up to 2300°C) leads to the severe embrittlement of the wire associated with the loss of fracture strength. In this work, we assess the transition behavior of pure and K-doped W wires exposed to the annealing in the temperature range of 1000-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…in the necking region) plastic deformation [34]. Indeed, as earlier studies show the determination of the true strain of the whole sample is complicated due to the formation of multiple necking regions [24], while determination of the yield stress is somewhat unambigous because the fabrication of standardized samples from 150 µm wire is impossible. Correspondingly, here we report the ultimate tensilie strength (UTS) which was measured at 22°C (RT), 300°C and 500°C for the two sets of wires annealed in the temperature range 1000-2300°C.…”
Section: Overview Of the Mechanical Properties Obtained From Tensile mentioning
confidence: 99%
See 4 more Smart Citations
“…in the necking region) plastic deformation [34]. Indeed, as earlier studies show the determination of the true strain of the whole sample is complicated due to the formation of multiple necking regions [24], while determination of the yield stress is somewhat unambigous because the fabrication of standardized samples from 150 µm wire is impossible. Correspondingly, here we report the ultimate tensilie strength (UTS) which was measured at 22°C (RT), 300°C and 500°C for the two sets of wires annealed in the temperature range 1000-2300°C.…”
Section: Overview Of the Mechanical Properties Obtained From Tensile mentioning
confidence: 99%
“…Correspondingly, here we report the ultimate tensilie strength (UTS) which was measured at 22°C (RT), 300°C and 500°C for the two sets of wires annealed in the temperature range 1000-2300°C. The detailed description of the study of mechanical properties is reported in [24]. The UTS and important features of the fracture surface are summarized in Figs.…”
Section: Overview Of the Mechanical Properties Obtained From Tensile mentioning
confidence: 99%
See 3 more Smart Citations